Propuesta de acciones de enfermería para un cuidado paliativo al paciente diabético Licán, Riobamba 2017. - Sani Yumisaca, Fanny Noemí (2017)
The research work entitled "Proposal of nursing actions for a palliative care to the diabetic patient Lican, Riobamba, 2017", aimed to propose nursing actions aimed at the palliative care of the diabetic patient, from a family and community approach. The research was carried descriptive, transversal; to determine the knowledge of patients; Field and documentary. The study population comprised 41 patients with a diagnosis of diabetes mellitus, for the data collection was used the survey, direct observation, and through two questionnaires. The first, closed "Quality of life and satisfaction in patients scale", taken from Peña Coba et al., Adapted by Figueredo, who made with minimum adjustments for its application to the Ecuadorian cultural context. The second, called "Instrument for Measuring Lifestyle in Diabetics (IMEVID)", validated by López-Carmona et al. Which will offer the possibility of measuring the lifestyle in patients with diabetes mellitus.The results obtained indicate that: the female sex is more affected with 75.61%, the average age of the patients fluctuated between 65 years and 75.61% only culminated the primary education. It was evidenced that the lifestyle of the diabetic patient in relation to nutritional habits is not adequate because not all patients follow a diabetic diet and because they continue to consume salt and sugar daily, 4.88% of the total Population almost never perform physical activity and 12.20% of patients follow medical instructions sometimes which predisposes the diabetic patient to present acute complications, chronic and states of depression; Which is why nursing actions are indicated with a palliative care to achieve a correct teaching and improve their lifestyles, providing comfort and well-being to the patient, family and community from a holistic point, respecting their culture and belief.